2017
DOI: 10.1111/jph.12662
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhiza‐mediated resistance in tomato against Cladosporium fulvum‐induced mould disease

Abstract: Root colonization with arbuscular mycorrhizal fungi (AMF) enhances plant resistance particularly against soil-borne pathogenic fungi. In this study, mycorrhizal inoculation with Glomus mosseae (Gm) significantly alleviated tomato mould disease caused by the air-borne fungal pathogen, Cladosporium fulvum (Cf). The disease index (DI) in local leaves (receiving pathogen inoculation) and systemic leaves (just above the local leaf without pathogen inoculation) was 36.4% and 11.7% in mycorrhizal plants, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 28 publications
1
21
0
1
Order By: Relevance
“…Nevertheless, the investigation by Maffei et al (2014), examining different experimental biosystem consisting of tomato, Tomato yellow leaf curl Sardinia virus (TYLCSV) and Funneliformis mosseae, indicated attenuation of viral disease symptoms upon symbiosis. More recently, Wang et al (2018) showed that mycorrhization of tomato affected by Cladosporium fulvum (pathogenic mold) caused significant increase in activities of both superoxide dismutase and peroxidase, which correlated with decrease in H 2 O 2 level. We suspect that similar biological processes may explain reduced concentration of H 2 O 2 in viruspositive potato host, however molecular studies are necessary to confirm this presumption.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the investigation by Maffei et al (2014), examining different experimental biosystem consisting of tomato, Tomato yellow leaf curl Sardinia virus (TYLCSV) and Funneliformis mosseae, indicated attenuation of viral disease symptoms upon symbiosis. More recently, Wang et al (2018) showed that mycorrhization of tomato affected by Cladosporium fulvum (pathogenic mold) caused significant increase in activities of both superoxide dismutase and peroxidase, which correlated with decrease in H 2 O 2 level. We suspect that similar biological processes may explain reduced concentration of H 2 O 2 in viruspositive potato host, however molecular studies are necessary to confirm this presumption.…”
Section: Discussionmentioning
confidence: 99%
“…Botrytis cinerea Fruits and ornamental flowers [28] Gray mold [28] Up to 30% to 40% loss of strawberries [29] Blumeria graminis Wheat and barley [28] Mildews of grasses [28] 18% potential and 13% de facto loss of grains under current disease control [30] Colletotrichum spp. Fruits and vegetables [28] Anthracnose spots and blights [28] Losses >80% in tropical, sub-tropical and Mediterranean regions [31] Cladosporium fulvum Tomato [32] Tomato leaf mold [32] Loss of 10-25% during regular years [33] Fusarium spp.…”
Section: Fungal Pathogen Crops Disease Crop Loss (%)mentioning
confidence: 99%
“…AMF species represent a particularly important subset of soil microbes that are able to form mutualistic symbiotic relationships with the roots of > 80% of all land plants [ 18 20 ]. Mycorrhizal symbionts are key sources of plant nutrients, and these AMF species can also enhance host plant resistance to environmental stressors [ 21 , 22 ] and to pathogen infections [ 23 , 24 ]. Few studies to date, however, have conducted comprehensive evaluations of AMF in the rhizosphere soil associated with Ferula sinkiangensis , and current understanding of the diversity and distribution of these microbial communities remains limited.…”
Section: Introductionmentioning
confidence: 99%